The Use of Zeolite Material as a Filtration Media in Waste Treatment: Bibliometric Analysis - Oktaviani, Rosa (ASEAN Journal for Science and Engineering in Materials, 2025)
This study aims to show the profile of research trends related to zeolite adsorbent material as a filtration medium in waste treatment. The research method used is a literature study with bibliometric analysis. The articles used are 2018-2023 with a total of 287 articles. Keywords used in PoP software are sewage treatment, adsorbent, and zeolite. Article data was analyzed and obtained using Publish or Perish (PoP) software on the Google Scholar database. The results of the following publication trends are represented in the form of graphical visualizations, which are analyzed using VOSviewer software. The focus of this study is the research trend on the effectiveness of using zeolite adsorbent material as a filtration medium in waste treatment. The implications of this study are (1) This finding will provide an empirical basis for the development of the use of zeolite as an adsorbent material; (2) Traceability of data on trends and updates from research on the use of zeolite as an adsorbent material.